Post-Secular Identity? Developing a New Approach to Religion in International Relations and IR Studies - Joanna Kulska (MDPI AG, 2021)
In spite of the increasing presence of religion in international relations with various publications observing this presence and numerous authorities calling for the inclusion of religion into mainstream research, there is no universal consent to recognize religion’s role in IR. In our opinion, the only way to reconcile IR with the international reality in which religion has been and will remain present in the foreseeable future is for the researchers themselves to construct—especially those oriented towards broad, non-Western perspective—a new face of the discipline, the face which in this article we call the post-secular identity of IR study. Assuming that identity is first and foremost a form of knowledge that tells us how we can define ourselves against the background of the surrounding world, our purpose is to look at the post-secular identity from two different perspectives which are analyzed in the two distinctive parts of the paper. On one hand, post-secular identity would mean the socio-political but also cultural phenomenon of the “knowledge of the self” expressed in the form of ideas, interests and goals of various state and nonstate actors, both religious and secular ones, that are more or less conditioned by religious determinants. We propose looking at them through the prism of a new kind of “partnership” emerging as a result of post-secular thinking in the area of IR. On the other hand, we want to look at post-secular identity as the badly required transformation within the area of IR study that, as we claim, needs to construct more inclusive views of IR scholars adopting a deliberative and pluralistic approach to the reality they examine based on widening their epistemological and hermeneutical horizons. This redefinition would be framed by recognizing religion as rational and adopting the view that the limits of the scientific methods do not coincide with the boundaries of rationality. We also adopt the view that along with the cognitive expansion of the universe, the concept of transcendence has been broadened.